Engineering long-term antibacterial PLA packaging: Controlled release of thymol co-amorphous pairs via supercritical solvent impregnation - Valenzuela-Bascunan, X; Galotto-Lopez, M (ELSEVIER SCI LTD, 2026)
The rapid release of active compounds often limits the development of active food packaging with long-term antimicrobial effects. This study proposes an innovative and sustainable solution by integrating cocrystallization and supercritical fluid technologies to create a controlled-release system. Herein is investigated the impregnation of poly(lactic acid) (PLA) foams with thymol (THY)-phenazine (PHE) cocrystal pairs via supercritical solvent impregnation at 40 degrees C and 12-18 MPa, analyzing the impact of different isobaric cooling rates (0.3 and 1.5 degrees C/min) on particle deposition and release kinetics. Submicron THY-PHE co-amorphous pairs were successfully deposited within the PLA matrix, with particle size dependent on the cooling rate. These pairs exhibited significantly slower release kinetics than pure THY, with a release rate constant up to 12 times lower. Consequently, PLA foams loaded with THY-PHE pairs demonstrated prolonged antibacterial activity, completely inhibiting Staphylococcus aureus and Escherichia coli for up to 192 h with concentrations three times lower than those required for pure THY. This work presents a robust, environmentally friendly, method for engineering advanced packaging materials with tailored, long-term release of active agents.
Keywords: Antibacterial packaging; Controlled release; Thymol co-amorphous; PLA foams; Supercritical Solvent Impregnation